DPD REI RIAU DAN PEMERINTAH KOTA PEKANBARU DALAM MENGEMBANGKAN PERUMAHAN RAKYAT (2011-2013) - Junizan "; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The Rule and Regulation of Indonesia year 1945 verse 28-H has been madated that housing and resident are the base of human right where everyone has right to live properous fisically and mentally, stay and get life in well environment and healthy. This base principle has been accomodated too in the Rule and Regulation No. 39 year 1999 about human right as well as in the Rule and Regulation No. 1 year 2011 about housing resident area. Therefore, to guarantee the fulfillment that human right it has became obligation for the government as state organizer to respect, save and also fulfill it directly. In concreting this mandate of our Rule and Regulation, the government needs help from other side, that is developer. This developer here is Real Estate Indonesia (REI) is the assosiation of developers in ndonesia. REI is believed becomes the stakeholders of the government in concreting this mandate of our Rule and Regulation to prepare housings for Indonesian societies.This research has been done in Pekanbaru where the location was in DPD REI Riau Province. This research was qualitative research in which the informations were taken by deep interviews from some interviewers.The result of this research showed that the growth of the Riau economic development that made the need of housings in this area was growing fast too. As a result, this impacted to the resident bussiness in Riau Province that becomes brighter and gives prospect. Riau province is one of theprovincesin Indonesia that experiences fast economic development in Sumatra. In every year almost 10.000 residents built in Riau Province with majority in Pekanbaru. Nowadays, Riau is in the first position in this growth of the residents expansion in Sumatra. While in Indonesia, Riau Province is in the third position.Key words: DPD REI Riau, Housing,subsidy, governmentpolicy.